A framework for measuring and tracking the climate resilience of women in agrifood systems - Marimo, Pricilla; Anbacha, Abiyot; Puskur, Ranjitha; Bindu, C. R.; Malhotra, Aayushi; Kori, Pooja (2025)
Despite numerous studies that develop, highlight or adapt frameworks on resilience in general, there is a lack of frameworks and tools that measure and track the (climate) resilience of women in agrifood systems. A scoping review of scholarly and grey literature was conducted to assess available resilience frameworks and indicators, adapt relevant components and develop a new framework that is specific to measuring and tracking the resilience of women in agrifood systems. A total of 83 studies were included in the review. Studies that focus on individual resilience are almost non-existent, with most frameworks focusing on household- or community-level resilience. Only three studies were found that explicitly focus on women-centered resilience indicators. However, these studies are based on case studies from Asia or the Middle East, measure resilience at larger scales (household, community and country) and do not necessarily assess climate resilience. A number of studies that highlight gender and resilience aspects exist, but most do not explicitly include climate resilience, focus on agrifood systems, or include a framework or indicators. The proposed framework is anchored around resilience capacities—anticipatory, absorptive, adaptive and transformative. We propose four main indicator categories and indices that correspond to the capacities. The proposed framework and indicators can be adapted for different contexts, offering valuable tools to enhance the understanding, assessment and tracking of the climate resilience of women in agrifood systems. These tools can help in decision-making and the design of effective strategies to strengthen women’s resilience, ensuring they are better equipped to face climate-related challenges.